DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA KPP PRATAMA BANYUWANGI) - Septiyaningsih, Anis (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
This study aims to analyze the system e-filling, e-billing, and tax punishment of individual taxpayers in Kantor Pelayanan Pajak Pratama Banyuwangi. The data of this study were obtained from the questionnaire (primary) and some literature studies (secondary). Questionnaire in this research is disseminated to individual taxpayers registered in Kantor Pelayanan Pajak Pratama Banyuwangi with convinience sampling method. Techniques and methods of data analysis in this study using SPSS program version 22.0. The results of this study indicate that e-filling system and tax punishment have a significant effect on taxpayers compliance in Kantor Pelayanan Pajak Pratama Banyuwangi, while e-billing does not affect the compliance of WPOP in KPPP Banyuwangi.